1998
DOI: 10.1093/humrep/13.7.1793
|View full text |Cite
|
Sign up to set email alerts
|

Acute cerebrovascular accidents with severe ovarian hyperstimulation syndrome

Abstract: Cerebrovascular complications are by far the most serious side-effects of ovarian hyperstimulation syndrome. We report a case in which the patient developed cerebral infarction with right sided hemiplegia as a result of severe hyperstimulation syndrome after using a gonadotrophin-releasing hormone agonist for intracytoplasmic sperm injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We found 14 published case reports (1960 to present) of stroke in patients suffering from OHSS: six patients recovered with minimal or no sequelae, six were left with hemiparesis, and two died. [3][4][5][6] The MCA was occluded in six cases. While six cases were treated with IV heparin, there are no reports where intra-arterial thrombolysis was administered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found 14 published case reports (1960 to present) of stroke in patients suffering from OHSS: six patients recovered with minimal or no sequelae, six were left with hemiparesis, and two died. [3][4][5][6] The MCA was occluded in six cases. While six cases were treated with IV heparin, there are no reports where intra-arterial thrombolysis was administered.…”
mentioning
confidence: 99%
“…In several mammalian species, however, brainstem raphe neurons are known to project axons that terminate in supraependymal plexuses in the lateral ventricle, and these neurons have been hypothesized to release serotonin directly into the CSF. 2,3 Once in the CSF, serotonin can act on the 5-HT 1C receptors of the nearby and downstream choroid plexus to modulate the choroid's production of CSF. 4,5 In humans, serotonin metabolites have been described in lumbar CSF samples, and there have been attempts to correlate concentrations of these metabolites with a variety of behaviors, notably depression and aggression.…”
mentioning
confidence: 99%
“…However, high serum estrogen concentration, hemoconcentration, reduced circulating blood volume by exhaustion of intravascular volume, and reduced venous return secondary to ovarian enlargement and ascites are possible pathomechanisms [2,6,7] . Furthermore, thromboembolism in OHSS can be associated with other hypercoagulable states, such as antiphospholipid antibody syndrome, antithrombin III deficiency and activated protein C resistance [6,8,9] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the large body of literature investigating the pathophysiology and prevention of OHSS, only a few studies have been published so far about the natural course of this disorder, the clinical outcome of affected women, and useful predictors of paracentesis. A PubMed search using the search terms, OHSS, outcome, recovery, treatment, and paracentesis (search date April 20, 2015), yielded 68 studies with 27 reporting on clinical outcomes among women with OHSS [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. Enskog et al [8] found that severe OHSS developed in 18 out of 428 (4%) women after controlled ovarian stimulation/IVF and was associated with a higher prevalence of allergy and a higher live birth rate compared to women after controlled ovarian stimulation/IVF without OHSS.…”
Section: Introductionmentioning
confidence: 99%
“…However, complications may occur. For example, the risk of venous thrombosis is significantly elevated and ischemic stroke has been described as a rare, but severe complication of OHSS in a number of studies [20,21,22,23,24,25,26,27,28,29]. Other rare complications include severe liver damage [30] and forearm amputation after repeated axillary vein thrombosis [31].…”
Section: Introductionmentioning
confidence: 99%